A morphological assessment of palaeochannels along the Lower Chambal Valley, India. Issue 27 (13th December 2022) - Ranga, Vikram; Pani, Padmini
Abstract: This paper reports the morphology and land use/land cover of palaeochannels along the Chambal River and it explores the prospects of their revival. A total of 104 palaeochannels were identified covering a distance of 465 km. Further, the study has identified that palaeochannels have a natural valley structure that facilitates limited and seasonal water inundation at irregular places, forming pond-like structures. The ponds are a direct consequence of blockages of natural drainage, mainly, by human construction activities. It has been found that the palaeochannels, despite having a valley structure, have private ownership and have been under cultivation. Further, this paper explores revival prospects of the palaeochannels and ponds, including their inclusion in the Amrit Sarovar Scheme (a Government Scheme). These results are significant in understanding of the geomorphological evolution of the Chambal River and in the possibility of using the areas (palaeochannels and ponds) in a more meaningful way. Abstract : KEY POLICY HIGHLIGHTS: Palaeochannels identified in this study have a significant role in understanding the evolution of the Chambal River to its present morphology. This study is the first instance, where the ponds on the palaeochannels have been reported. The ponds can be developed as Amrit Sarovars (Nectar Ponds) under the Scheme of the Union Government of India by the same name. This study sheds light on the neglected/unreported features that can be magnates of further research.